Climate intervention research in the World Climate Research Programme: a perspective - Hurrell, James W.; Haywood, James M.; Lawrence, Peter J.; Lennard, Christopher J.; Oschlies, Andreas (Frontiers in Climate, 2024)
The 2023 World Climate Research Programme (WCRP) Open Science Conference underscored the critical need for increased climate change mitigation and adaptation efforts, along with enhanced climate knowledge and decision-making systems. This Perspective discusses climate intervention (CI) within WCRP’s research framework, emphasizing three main approaches: terrestrial carbon dioxide removal (CDR), marine CDR, and solar radiation modification (SRM). As global anthropogenic greenhouse gas emissions continue to rise, CI strategies are increasingly recognized as potentially critical supplements to traditional mitigation methods. We call for WCRP to take a leadership role in CI research, highlighting the need for inclusivity and collaboration, especially with researchers from the Global South, to establish a firm scientific foundation for an equitable and comprehensive assessment of the benefits and risks of CI approaches relative to the risks of anthropogenic climate change.